Sense of belonging and its positive association with physical activity levels and negative association with sedentary behaviors in residential aged care facilities in COVID-19 pandemic: a longitudinal study - Gonzalo Marchant; Emma Guillet-Descas; Natacha Heutte (Frontiers in Psychology)
IntroductionThe COVID-19 pandemic reduced physical activity levels and increased sedentary behavior among older adults in residential care facilities. Another effect of this crisis was that facilitating a sense of social belonging through in-person social activities, such as group exercises or communal meals, became difficult. This study examines the relationship between physical activity, sedentary behavior, and sense of social belonging in older adults.MethodsThis longitudinal study, which lasted 10 months, involved 57 older adults in residential care facilities. Participants completed the Échelle de mesure du Sentiment d’Appartenance Sociale (ESAS) questionnaire three times and wore an accelerometer on their waists for 1 week each time to measure sedentary time and physical activity levels. The ESAS questionnaire, a validated tool for evaluating social belonging in older adults, measures social belonging through a series of questions that assess an individual’s feelings of acceptance and intimacy within their social group.ResultsParticipants were predominantly sedentary (7.30 h/day) and engaged in low-intensity physical activities (2.9 h/day). They did not meet the recommended 150 min/week of moderate-to-vigorous physical activity. The sense of social belonging was high, with mean scores of 6.75 (ESAS), 7.08 (Acceptance), and 6.43 (Intimacy). Light physical activity was negatively associated with sedentary time. The sense of social belonging was positively associated with light physical activity and negatively correlated to sedentary time.ConclusionThis study underscores the importance of light physical activity and a sense of social belonging in reducing sedentary behavior among older adults in residential care facilities. By promoting social interactions and light physical activity, we can enhance the well-being of this population, especially during pandemic conditions. The study’s findings should inspire future interventions to focus on these aspects, thereby improving health outcomes in residential care facilities for older adults.